The “genius loci” of places that experience intense tourism development - Christou, Prokopis A.; Farmaki, Anna; Saveriades, Alexis; Spanou-Tripinioti, Elena (My University, 2019)
In classical Rome, the icon of a snake was used to depict the protection of place identity. This genius loci helped identify the quintessential elements of a place. The present study explores the extent to which places experiencing significant tourism development have lost their genius loci. Findings are derived from a comparative appraisal of archival and current landscape photographs, supported by an exploratory study at a particular setting. The fieldwork reveals that tourism activity is predominantly accountable for changes in a place's genius loci and that certain sites seem to possess attributes that retain that “genius”. Points of reference are identified so that destinations can regain their lost genius loci.
Keywords: Cyprus; Genius loci; Sustainable tourism; Tourist experience; Tourism development